湄洲湾表层沉积物中多环芳烃的含量分布及来源分析 - 林建清; 王新红; 洪华生; 陈伟琪; 刘日先; 黄哲强; L IN Jianqing; WANG Xinhong; HONG Huasheng; CHEN Weiqi; L IU Rixian; HUANG Zheqiang (《厦门大学学报（自然科学版）》编辑部, 2003)
[摘要]：2000 年10 月在湄洲湾海域6 个站位采集表层沉积物样,采用GC/ MS 法分析其多环芳烃的含量. 结果显示: 在这些沉积物样中,美国环保署优控的16 种多环芳烃的含量分布较为均匀,其范围为196. 7～299. 7 ng/ g ,平均值为 256. 1 ng/ g ;显著低于长江口、珠江口及其欧美主要港口表层沉积物中多环芳烃的含量. 对多环芳烃特征组分的比值 (菲/ 蒽比值,荧蒽/ 芘比值) 及16 种多环芳烃中四、五和六环总含量的百分比的分析表明:湄洲湾表层沉积物的多环 芳烃主要来源于燃料的高温燃烧.[Abstract]:The Meizhou Bay , located in the mid2east coast of Fujian , China , is a semi2enclosed narrow bay st retching deep into the inland with favorable hydrological circulation conditions. With the const ruction of port s , oil2refinery works and power indust ry in the coastal area ,PAHs’pollution is a potential environmental risk factor in this marine environment ,but no data of PAHs level in this marine environment were established before. The aim of this study is to examine PAHs’dist ribution in the surface sediment s and analyze their sources in the Meizhou Bay. The data showed that : PAHs’concent rations in the surface sediment s were f rom 196. 7 ～ 299. 7 ng/ g and average value was 256. 1 ng/ g. The result s revealed that PAHs’pollution in the sediment was similar. The result s also showed that sediment PAHs in the Meizhou Bay were much lower than those in the Pearl River Delta and the Yangtze River Delta and the major harbors in America and Aust ralia but higher than that in the surface sediment s of White Sea. Ratio values of specific PAH compounds such as phenanthrene/ anthracene and fluoranthene/ pyrene were calculated to evaluate the possible source of PAHs contamination in the surface sedi2 ment s of the Meizhou Bay ,the percentage of 4 + 5 + 6 rings of PAHs in total was also used to indicate PAHs’ possible sources. The result s suggested that the surface sediment s might mainly have pyrolytic input s of PAHs. 国家自然科学基金(A20077023 ,C40106012) 资助